A patch of blue [videorecording (DVD)] - Green, Guy, 1913-2005; Poitier, Sidney; Winters, Shelley; Hartman, Elizabeth, 1943-1987; Ford, Wallace, 1898-1966; Dixon, Ivan, 1931-2008; Fraser, Elisabeth, 1920-2005; Qualen, John, 1899-1987; Goldsmith, Jerry; Burks, L. Robert, 1909-1968; Roland, Rita; Kata, Elizabeth (Archive collection., 2014)
Raised by a bigoted, abusive mother, an awkward, blind, white woman does not know that the man helping her around is black.